THE IMPACT OF MONETARY FINANCE IN THE GENERAL BUDGET IN IRAQ - Ali Abdulkadhim Dadoosh; Prof, Dr. Faris Kareem Buraihi (Scholar Express Journals, 2024)
The study addressed Monetary Finance policy as a macroeconomic policy to confront crises in Iraq and selected countries. Monetary Finance involves direct transfer of funds from the central bank to the central government in exchange for government securities (deductible transfers) provided to the central bank. Monetary Finance also includes creating money by the central bank to finance public spending, cover deficits and government debt at low interest rates, usually lower than the market rate. The study utilized the Financial Crisis with Dummy variable - NARDL model to analyze the impact of monetary finance on the general budget. The study found that monetary finance had a positive effect on financing deficits and public debt in Iraq. However, it led to an increase in the money supply, resulting in higher inflation levels especially after 2020. The study aimed to understand monetary finance as a policy imposed by governments on central banks to finance public expenditure during crises. and the study lies in how monetary finance contributes to addressing crises affecting the Iraqi economy such as financial deficits and rising public debt. Monetary Finance also increases the monetary base, leading to inflation and weakening the control of the Iraqi Central Bank
Keywords: Monetary Finance; General Budget; Asymmetric Non-linear Autoregressive Distributed Lag